Development of Physical and Earth and Space Science Content Problems Based on PISA in Class VIII Junior High School - Nely Andriani; Benni Benni; Zulherman Zulherman; Sudirman Sudirman (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2018)
PISA-based science problem instruments have been developed on physical, earth and space content that is valid, practical and reliable. The PISA-based question instrument was developed used as one of the teaching materials in science learning in junior high school so students are familiar with the problem of metacognitive dimensions.The development model used is the development model of Borg and Gall. The subject of this study is a PISA-based science problem instrument for earth and space physical and content content. Data were collected using walkthroughs, questionnaires, and tests. While the instruments of data collection using a validation sheet, questionnaire questionnaire, and test questions. The data obtained were then analyzed descriptively. The results showed that the product developed was very valid with an average of 4.6; practical with an average of 0.88; and reliable with an average of 0.88. Based on the results of the research obtained, it was concluded that the PISA-based science problem instrument for physical content and earth and space content is feasible to use.